ELEMENTAL MUSIC-MAKING AS A HEALTH SAVING PHENOMENON IN THE SYSTEM OF GENERAL EDUCATION - N. V. Golubeva (Russian State Vocational Pedagogical University, 2015)
The paper aims at drawing the attention of teaching community to the health promoting potential of music making disregarded nowadays by educational establishments. The traditional musical education focused mainly on musicology leads to artificial intellectualization, and leaves no room for chil-dren's imagination, intuition, creativity, joyful feelings and activities.The author discusses the specificity of the music teaching concept, developed by Carl Orff and his followers, and based on the complex understanding of human nature, history, living conditions, and corresponding with genetic laws. On the one hand, the music-making involves consideration of the learners' psychological features and individual propensities, and on the other hand, it has a syncretic effect on the main psychological and physiological functions including communication, speech, motion, etc. As the result, it resists the hypodynamia and fatigue, and promotes health.The paper reveals the experience of the Music Education Department in the Institute of Psychology and Pedagogy of Tumen State University, providing specializations in the Elemental Music-Making in Educational Process and Health Saving Potential of Music Teaching. The outcomes of the practical seminars and experimental teaching in the Primary School № 3 in Pytyah Town of Khanty-Mansi Autonomous Region confirm the author's theory of the positive emotional impact of music-making on the learning and health saving activities.